2013
DOI: 10.1063/1.4792942
|View full text |Cite
|
Sign up to set email alerts
|

Controlled polarity of sputter-deposited aluminum nitride on metals observed by aberration corrected scanning transmission electron microscopy

Abstract: The polarity determination process of sputter-deposited aluminum nitride (AlN) on metals has been analyzed using aberration corrected atomic resolution scanning transmission electron microscope. Direct growth of c-axis orientated AlN on face centered cubic metals (fcc) (111) with the local epitaxy has been observed, and the polarity was determined at the AlN/metal interface. We found that the AlN polarity can be controlled by the base metal layer: N-polarity AlN grows on Pt(111) while Al-polarity AlN forms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…AlN was deposited from a gun with an Al target and metallic Pt from another gun with a Pt target. Details of the deposition conditions were given in our previous report (Harumoto et al, 2013). It should be noted that a small number of nitrogen atoms are incorporated into the Pt lattice when the Pt film is deposited under Ar-N 2 atmosphere.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…AlN was deposited from a gun with an Al target and metallic Pt from another gun with a Pt target. Details of the deposition conditions were given in our previous report (Harumoto et al, 2013). It should be noted that a small number of nitrogen atoms are incorporated into the Pt lattice when the Pt film is deposited under Ar-N 2 atmosphere.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…In addition, it is reported that the polarity distribution of the piezoelectric film has a strong impact on the etch behavior. 16,21 Bulk AlN which shows N-polarity is etched faster in a wet-chemical etching solution (KOH, H3PO4) than AlN with Al-polarity. 14 The considerable lower |d33| values of the AlN synthesized on Ti films support the assumption of a mixed Al-and N-polarity of the layer.…”
Section: Resultsmentioning
confidence: 99%
“…These nanoscale voids could be the result of the incomplete coalescence of the nucleation islands. Literatures proposed that a few monolayers of Al were deposited on the sapphire's surface [29,30] and formed the nucleation islands before NH3 came into the reaction chamber, creating a quasi-threedimensional (quasi 3D) growth mode at the beginning of the growth. Later, the high-temperature AlN began to grow on these quasi-3D islands, which was followed by the islands' coalescing and finally the growth transferred to a 2D mechanism.…”
Section: Resultsmentioning
confidence: 99%